ПЕРИАППЕНДИЦИТ КАК ПРИЧИНА НЕОБОСНОВАННОГО УДАЛЕНИЯ ЧЕРВЕОБРАЗНОГО ОТРОСТКА У ЖЕНЩИН РЕПРОДУКТИВНОГО ВОЗРАСТА - Гринцов, А. Г.; Матийцив, А. Б.; Пилюгин, Г. Г.; Христуленко, А. А. (University Clinic; No 3(32) (2019): UNIVERSITY CLINIC, 2019)
In this work, the morphological changes in the remote worm-shaped processes have been retrospectively analyzed. It has been established that in 7.48% of the samples, the inflammatory process mainly extends to the serous and subserous membranes and is represented by single eosinophils, lymphocytes. Visualization during laparoscopy of the phenomena of periappendicitis (serositis) and removal of the latter during surgery is an indication for further examination of patients. It has been established that in most cases the phenomenon of periappendicitis is caused by infection of the pelvic organs in women of reproductive age.